Inositol and antioxidant supplementation: Safety and efficacy in pregnancy. Issue 5 (10th April 2019) - Formoso, Gloria; Baldassarre, Maria P.A.; Ginestra, Federica; Carlucci, Maria Assunta; Bucci, Ines; Consoli, Agostino
Summary: Pregnancies complicated by diabetes have largely increased in number over the last 50 years. Pregnancy is characterized by a physiologic increase in insulin resistance, which, associated with increased oxidative stress and inflammations, could induce alterations of glucose metabolism and diabetes. If not optimally controlled, these conditions have a negative impact on maternal and foetal outcomes. To date, one can resort only to diet and lifestyle to treat obesity and insulin resistance during pregnancy, and insulin remains the only therapeutic option to manage diabetes during pregnancy. However, in the last years, in a variety of experimental models, inositol and antioxidants supplementation have shown insulin‐sensitizing, anti‐inflammatory, and antioxidant properties, which could be mediated by some possible complementary mechanism of action. Different isomers and multiple combinations of these compounds are presently available: Aim of the present review article is to examine the existing evidence in order to clarify and/or define the effects of different inositol‐ and antioxidant‐based supplements during pregnancy complicated by insulin resistance and/or by diabetes. This could help the clinician's evaluation and choice of the appropriate supplementation regimen.